2011
DOI: 10.1080/01904167.2011.544529
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Nitrogen-Utilization Efficiency in Wheat Genotypes Differing in Nitrate Reductase Activity

Abstract: 2 The plants growing in natural field conditions do not express their full genetic potential of nitrogen (N) utilization due to a limiting availability of N at later stages of growth. Their full potential is likely to manifest under non-limiting nitrogen supply wherein the high nitrate reductase (HNR) and the low nitrate reductase (LNR) genotypes should differ significantly in their N-utilization efficiencies. In a sand culture experiment, using IC 321157 (HNR) and C 306 (LNR) genotypes of Triticum aestivum L.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 26 publications
1
8
0
Order By: Relevance
“…Our results showed that KNO 3 source significantly increased the activities of nitrogen metabolizing enzymes and aminotransferases as also reported by Jain et al (2011);Anjana et al (2011);Asthir and Bhatia (2014);Hawkesford (2014). Whereas, NH 4 Cl elevated activities of GS-GOGAT and aminotransferases (GOT and GPT) along with increase in acid and neutral invertase activities in shoot as well as in root which indicated that unregulated uptake of ammonium supplied as a single nitrogen source is considered to exert a carbon stress on plant roots for its assimilation and subsequent translocation to shoots (Lewis et al 1987;Britto and Kronzucker 2002).…”
Section: Discussionsupporting
confidence: 90%
“…Our results showed that KNO 3 source significantly increased the activities of nitrogen metabolizing enzymes and aminotransferases as also reported by Jain et al (2011);Anjana et al (2011);Asthir and Bhatia (2014);Hawkesford (2014). Whereas, NH 4 Cl elevated activities of GS-GOGAT and aminotransferases (GOT and GPT) along with increase in acid and neutral invertase activities in shoot as well as in root which indicated that unregulated uptake of ammonium supplied as a single nitrogen source is considered to exert a carbon stress on plant roots for its assimilation and subsequent translocation to shoots (Lewis et al 1987;Britto and Kronzucker 2002).…”
Section: Discussionsupporting
confidence: 90%
“…Earlier reports using maize as a model plant, revealed a decreasing trend of N uptake and assimilation at leaf ageing and that the decrease was enhanced when plants were N starved (Hirel et al, 2005). However, reverse trend was observed in crops raised under higher levels of N, which revealed coordinated increase in the activities of all N assimilating enzymes (Anjana et al, 2011). In this study, we elaborated N assimilation in diverse genotypes raised under different N levels to understand biochemical basis of source sink transition of wheat leaves in relation to their variability.…”
Section: Discussionmentioning
confidence: 94%
“…In the recent study Anjana et al (2011) in 15 days old seedlings grown under non limiting N supply, conclusively showed that it was the coordinated increase in the activity of all the enzymes in the N assimilatory pathway in HNR genotype. The present studies were carried out at seedling stage as well as at various growth stages.…”
Section: Discussionmentioning
confidence: 95%